Comparative study on the machinability aspects of aluminium-silicon carbide and aluminium-graphite-silicon carbide hybrid composites. (27th June 2011) - Krishnamurthy, L.; Sridhara, B.K.; Abdul Budan, D.
Aluminium matrix particulate composites are one of the materials finding wide ranging applications in automobile, aerospace and military industries because of their attractive properties such as high strength to weight ratio, high wear resistance, high temperature stability, etc. Though most engineering components aluminium matrix particulate composites are primarily manufactured in near net shape, machining is often required for tolerance and surface integrity control. This paper presents the result of an experimental investigation on the comparative machinability of aluminium-silicon carbide composites and aluminium-graphite-silicon carbide hybrid composites during turning using carbide tool inserts. The experiments have been carried out based on central composite design of experiments approach. The influence of machining parameters viz. cutting speed, feed and depth of cut on the resultant force has been analysed statistically. It is established that hybrid composites have better machinability when compared to aluminium-silicon carbide composites. Contour plots of constant resultant force have been developed for Al-SiC and Al-Graphite-SiC hybrid composites.